Testing the feasibility of a sustainable preschool obesity prevention approach: a mixed-methods service evaluation of a volunteer-led HENRY programme - Howlett, Neil; Roberts, Kim P. J.; Swanston, Di; Edmunds, Laurel D.; Willis, Thomas A. (BMC public health, 2021)
Background Over the last 10 years HENRY has been working to reduce and prevent child obesity by training health and early years professionals to deliver its evidence-based programme to parents. The aim and unique contribution of this study was to evaluate whether training volunteers to deliver this programme on a one-to-one basis was feasible. Methods Mixed-methods service evaluation with parent-reported pre- and post-programme outcomes and focus groups conducted with parents and volunteer facilitators. The programme consisted of 8 one-to-one sessions delivered weekly by volunteers ( n = 18) to build food and activity-related knowledge, skills, and understanding, and improve parenting efficacy, and parent and child eating and physical activity. Programmes took place at parent’s ( n = 69) home or local community venues in four London boroughs, United Kingdom. Parent-reported parenting efficacy, emotional wellbeing, eating, and physical activity data were captured, alongside parent ratings of the programme and volunteer ratings of the training. Parent and volunteer focus groups explored involvement, expectations, and experiences of the programme, training and delivery, feedback, and impact. Results Parents were mostly female, had varied ethnic backgrounds, and were often not working but well educated. There were statistically significant improvements of a medium-to-large size in parent and child emotional wellbeing, parenting efficacy, fruit and vegetable consumption, family eating and food purchasing behaviours. Parent ratings of the programme were positive and qualitative data highlighted the holistic nature of the programme, which focused on more than just food, and the relationships with volunteers as key facets. Volunteers were also mostly female, had varied ethnic backgrounds, and were often well educated, but more likely to be employed than parents. Volunteers rated the training and delivery as useful in enabling them to deliver the programme confidently and for their own wellbeing. Despite finding some sessions challenging emotionally, volunteers reported positive family lifestyle improvements by parents and children and that the experience would be useful for future employment. Conclusions It is feasible to recruit and train volunteers to deliver a structured preschool obesity prevention programme, which parents considered acceptable and enjoyable, with preliminary reports of parent and child benefits.